The Effect of The Covid-19 Pandemic on The Amount of Waste at The Toisapu Final Processing Site (TPA) Ambon City, Maluku Province - Mutmainnah, Heni; Pandiangan, Fajar Akbar (Universitas Sembilanbelas November Kolaka, 2022)
The massive Covid-19 pandemic has caused countries to implement policies in the form of social restrictions to limit activities outside and only carry out activities indoors. The risk of contracting the Covid-19 virus causes a reduction in public activities in the form of commercial, institutional, and public service facilities. This has an impact on the amount of waste generated by people in urban areas during the pandemic. Therefore, this study aims to determine the effect of covid-19 on the amount of waste that enters the Toisapu TPS in Ambon city and to see the difference in the average amount of waste before the pandemic and during the COVID-19 pandemic with Paired Sample T Test analysis using IBM SPSS statistics 25 application. The results showed that there was a correlation between the two variables (0.693) which means that the correlation of the amount of waste entering the Toisapu TPS between before and during covid-19 was strong but not significant as indicated by the probability value (sig.) 0.013 0.05. While the calculated t value is 3.16 2.63 (t table value) so it can be concluded that the average amount of waste before and during the Covid-19 period is different. Keywords: Pandemic, waste, T test